ВЕЙВЛЕТ АНАЛИЗ ПРОЦЕССОВ АКТИВНОСТИ КВАЗАРА 3С273 В РАДИО-РЕНТГЕНЕ-УЛЬТРАФИОЛЕТЕ - Рябов, М. И.; Сухарев, А. Л. (Одеські астрономічні публікації, 2011)
Dynamics of development of activity process of a quasar 3С273 according to published data of radio (Green Bank, Algonquin, UMRAO, Haystack, Metsahovi, Itapetinga, Crimea), ultra-violet (IUE, XMM-Newton) and x-ray (RXTE, CGRO, GINGA, ASCA, EXOSAT, HEAO2, GRANAT, ROSAT) supervision are investigated. Periodogram and wavelet analysis methods are applied for definition of the basic periods of variability in each range and dynamics of their changes for 30-40 years of observation. Properties of the separate periods of acti-vity during 6-8 years are considered. On spectral indexes, time shifts, spectra of maximum activity and data VLBI of observation properties of extreme displays of activity in system «core-accretion disk-jet» are defined.